Designing a Model of the Tendency Toward Domestic Violence Based on Behavioral Brain Systems with the Mediating Role of Psychological Capital in Women Affected by Marital Infidelity - Siaha , Ali; Farhangi, Abdolhassn; Mohammadi Aria, Alireza (Mental Health and Lifestyle Journal, 2026)
The present study aimed to design a model of the tendency toward domestic violence based on behavioral brain systems, with the mediating role of psychological capital in women affected by marital infidelity. The research method was descriptive-correlational. The research population included all women dealing with the issue of spousal infidelity who were clients at the Shiva Counseling and Psychology Center in Tehran during 2025. To determine the sample size, based on Kline (2010), 323 participants were selected as the sample using the convenience sampling method. Structural Equation Modeling (SEM) using SPSS22 and Amos23 software was employed for data analysis. Data collection instruments included the Marital Infidelity Questionnaire (Yenisey & Kökdemir, 2006), the Psychological Capital Questionnaire (Luthans, 2007), the Domestic Violence Questionnaire (Tabrizi et al., 2012), and Gray’s Behavioral Brain Systems Questionnaire (Gray, 1989). The results showed that the components of behavioral brain systems—Approach ( ), Active Avoidance ( ), Passive Avoida The present study aimed to design a model of the tendency toward domestic violence based on behavioral brain systems, with the mediating role of psychological capital in women affected by marital infidelity. The research method was descriptive-correlational. The research population included all women dealing with the issue of spousal infidelity who were clients at the Shiva Counseling and Psychology Center in Tehran during 2025. To determine the sample size, based on Kline (2010), 323 participants were selected as the sample using the convenience sampling method. Structural Equation Modeling (SEM) using SPSS22 and Amos23 software was employed for data analysis. Data collection instruments included the Marital Infidelity Questionnaire (Yenisey & Kökdemir, 2006), the Psychological Capital Questionnaire (Luthans, 2007), the Domestic Violence Questionnaire (Tabrizi et al., 2012), and Gray’s Behavioral Brain Systems Questionnaire (Gray, 1989). The results showed that the components of behavioral brain systems—Approach ( ), Active Avoidance ( ), Passive Avoidance ( ), Extinction ( ), and Escape ( )—had a significant negative effect on the tendency toward violence ( ). However, Fight ( ) had a significant direct effect on the tendency toward violence ( ). Further results indicated that behavioral brain systems had a significant indirect effect on the tendency toward violence in women affected by marital infidelity through the mediation of psychological capital ( ). Accordingly, the proposed research model demonstrated a good fit. Empirically, this model provides a structured basis for examining targeted interventions that focus not only on managing behavioral brain system responses but also on restoring psychological capital by fostering resilience and enhancing hope. nce ( ), Extinction ( ), and Escape ( )—had a significant negative effect on the tendency toward violence ( ). However, Fight ( ) had a significant direct effect on the tendency toward violence ( ). Further results indicated that behavioral brain systems had a significant indirect effect on the tendency toward violence in women affected by marital infidelity through the mediation of psychological capital ( ). Accordingly, the proposed research model demonstrated a good fit. Empirically, this model provides a structured basis for examining targeted interventions that focus not only on managing behavioral brain system responses but also on restoring psychological capital by fostering resilience and enhancing hope.